Population Projection and Growth Rate using Leslie Matrix Model for Female Resource Mapping - Sari, Nofi Triana; Isnurani, Isnurani; Basir, Choirul (Semarak International Journal of Current Research in Language and Human Studies, 2025)
The Leslie matrix is a mathematical model used to predict the number and growth rate of the female population. Fertility and survival rates of women are internal factors in the Leslie matrix that can affect the size of a population. The purpose of this study is to implement the Leslie matrix model in projecting the number and growth rate of the female population in each age group in West Jakarta City. The research method used is quantitative descriptive research, determining the object of research, analyzing the data that has been processed using the Python programming language, and drawing conclusions. The research data used in this study is secondary data with the number of female residents and the number of children born based on the age of the mother in 2018-2023. The result of this research is a Leslie matrix model for the female population in West Jakarta City with 16 age intervals constructed using the value of fertility and survival rates. The conclusion of this research is that the eigenvalue of 0.8613 is obtained and the population decreases in the following year and it can be said that the female population growth rate in West Jakarta City tends to be negative, which is 13.8703%.